A mouse model of non-motor symptoms in Parkinson's disease: focus on pharmacological interventions targeting affective dysfunctions - Bonito-Oliva, Alessandra; Masini, Débora; Fisone, Gilberto (Frontiers in Behavioral Neuroscience, 2014)
Non-motor symptoms, including psychiatric disorders, are increasingly recognized as a major challenge in the treatment of Parkinson’s disease (PD). These ailments, which often appear in the early stage of the disease, affect a large number of patients and are only partly resolved by conventional antiparkinsonian medications, such as L-DOPA. Here, we investigated non-motor symptoms of PD in a mouse model based on bilateral injection of the toxin 6-hydroxydopamine (6-OHDA) in the dorsal striatum. This model presented only subtle gait modifications, which did not affect horizontal motor activity in the open-field test. Bilateral 6-OHDA lesion also impaired olfactory discrimination, in line with the anosmia typically observed in early stage parkinsonism. The effect of 6-OHDA was then examined for mood-related dysfunctions. Lesioned mice showed increased immobility in the forced swim test and tail suspension test, two behavioral paradigms of depression. Moreover, the lesion exerted anxiogenic effects, as shown by reduced time spent in the open arms, in the elevated plus maze test, and by increased thigmotaxis in the open-field test. L-DOPA did not modify depressive- and anxiety-like behaviors, which were instead counteracted by the dopamine D2/D3 receptor agonist, pramipexole. Reboxetine, a noradrenaline reuptake inhibitor, was also able to prevent the depressive and anxiogenic effects produced by the lesion with 6-OHDA. Interestingly, pre-treatment with desipramine prior to injection of 6-OHDA, which is commonly used to preserve noradrenaline neurons, did not modify the effect of the lesion on depressive- and anxiety-like behaviors. Thus, in the present model, mood-related conditions are independent of the reduction of noradrenaline caused by 6-OHDA. Based on these findings we propose that the anti-depressive and anxiolytic action of reboxetine is mediated by promoting dopamine transmission through blockade of dopamine uptake from residual noradrenergic terminals.